2000
DOI: 10.1128/mcb.20.18.6741-6754.2000
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling between Phenotypic Senescence and Cell Cycle Arrest in Aging p21-Deficient Fibroblasts

Abstract: Irreversible G 1 arrest in senescent human fibroblasts is mediated by two inhibitors of cyclin-dependent kinases (Cdks), p21Cip1/SDI1/WAF1 and p16 Ink4A . To determine the physiological and molecular events that specifically require p21, we studied senescence in human diploid fibroblasts expressing the human papillomavirus type 16 E6 oncogene, which confers low p21 levels via enhanced p53 degradation. We show that in late-passage E6 cells, high Cdk activity drives the cell cycle, but population expansion is sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
78
2
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 69 publications
(123 reference statements)
12
78
2
3
Order By: Relevance
“…It is possible that MnSOD-induced accumulation of p21 protein levels would protect cyclin E(A)-Cdk 2 kinase complexes, which upon subculturing would facilitate a Rb phosphorylation-independent entry into S-phase. Such an assumption is supported by previous studies in the literature demonstrating cyclin E-dependent and Rb phosphorylationindependent entry into S-phase (24,52). Nonetheless, the observation that MnSOD induces p21 protein levels might be of broad interest because of the possibility that antioxidants, in particular MnSOD, could have a protective role in maintaining the reproductive integrity of a variety of proliferation-competent quiescent cells, including stem cells.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It is possible that MnSOD-induced accumulation of p21 protein levels would protect cyclin E(A)-Cdk 2 kinase complexes, which upon subculturing would facilitate a Rb phosphorylation-independent entry into S-phase. Such an assumption is supported by previous studies in the literature demonstrating cyclin E-dependent and Rb phosphorylationindependent entry into S-phase (24,52). Nonetheless, the observation that MnSOD induces p21 protein levels might be of broad interest because of the possibility that antioxidants, in particular MnSOD, could have a protective role in maintaining the reproductive integrity of a variety of proliferation-competent quiescent cells, including stem cells.…”
Section: Discussionsupporting
confidence: 62%
“…Increases in both p16 and p21 Cdk inhibitors during an irreversible growth arrest are generally thought to be associated with accumulation of hypophosphorylated Rb (24). Hypophosphorylated Rb is known to sequester members of the E2F transcription factor family, and the unavailability of E2F inhibits progression through the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, previous work has established that CDK2 kinase activity (but not CDK2 protein levels) is decreased during replicative senescence (13)(14)(15)36). Expression of recombinant CYCLIN E-CDK2 in replicatively senescent human fibroblasts resulted in DNA synthesis in approximately 10% of cells (17).…”
Section: Ink4amentioning
confidence: 99%
“…Cip1 , whereas CDK2 protein levels remain unchanged (13)(14)(15); whereas in replicative senescence of cultured human umbilical vein endothelial cells (HUVEC), reduction of both CDK2 activity and protein levels were noted (16). Transduction of replicatively senescent cells with Cyclin E-CDK2 complexes results in cellcycle reentry in a subset of cells, indicating that reduction of CDK2 activity is indeed essential for replicative senescence (17).…”
Section: Ink4cmentioning
confidence: 99%
“…Senescence is also a tumor suppressor mechanism that prevents emergence of transformed cells (9). It has been shown that lack of p21 delays or abolishes the onset of senescence (12) and that continuous p21 expression induces a senescent arrest in normal and cancer cells in a p53-independent manner (13)(14)(15).…”
Section: Kip2mentioning
confidence: 99%